Enhanced hydrogen spillover to fullerene at ambient temperature. Issue 27 (9th February 2018) - Nishihara, Hirotomo; Simura, Tomoya; Kyotani, Takashi
Abstract : Enhanced hydrogen spillover on molecular fullerene C60, which represents extremely curved graphene sheets, is experimentally demonstrated around ambient temperature. Since the spillover hydrogen is strongly attracted by C60, the increase of C60 mass can be directly confirmed by mass spectroscopy. Abstract : Enhanced hydrogen spillover on molecular fullerene C60, which represents extremely curved graphene sheets, is experimentally demonstrated around ambient temperature. Since the spillover hydrogen is strongly attracted by C60, the increase of C60 mass can be directly confirmed by mass spectroscopy.